2020
DOI: 10.1101/2020.05.21.102756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A natural single-guide RNA repurposes Cas9 to autoregulate CRISPR-Cas expression

Abstract: CRISPR-Cas systems provide their prokaryotic hosts with acquired immunity against viruses and other foreign genetic elements, but how these systems are regulated to prevent auto-immunity is poorly understood. In type II CRISPR-Cas systems, a transactivating CRISPR RNA (tracrRNA) scaffold functions together with a CRISPR RNA (crRNA) guide to program Cas9 for the recognition and cleavage of foreign DNA targets. Here, we show that a long-form tracrRNA performs an unexpected second function by folding into a natur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…In contrast to the Cas3 nuclease, localization of Cas9 in the nucleoid could pose autoimmunity risks. In fact, a recent study showed that uncontrolled induction Cas9 in S. pyogenes, which occurs in the absence of a natural single guide RNA, results in increased self-targeting and auto immunity (Workman et al, 2020). Anecdotally, we have also observed that activity of Listeria monocytogenes Cas9 is very low, at least in laboratory conditions (Rauch et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast to the Cas3 nuclease, localization of Cas9 in the nucleoid could pose autoimmunity risks. In fact, a recent study showed that uncontrolled induction Cas9 in S. pyogenes, which occurs in the absence of a natural single guide RNA, results in increased self-targeting and auto immunity (Workman et al, 2020). Anecdotally, we have also observed that activity of Listeria monocytogenes Cas9 is very low, at least in laboratory conditions (Rauch et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
“…The molecular basis for most of these alternative functions of Cas proteins are not well understood. A recent study showing SpyCas9 can repress its own promoter using a natural single guide opens the possibility that CRISPR-Cas systems can also function as intrinsic transcriptional regulators (Workman et al, 2020). It is therefore possible that crRNAs generated from degenerate selftargeting spacers might direct CRISPR-Cas enzymes in regulating host genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not what is observed in nature, when CRISPR-Cas reactivity is usually low (Hynes et al, 2017). In addition, scientists can easily generate CRISPR-Cas systems with higher reactivities (Heler et al, 2017; Levy et al, 2015; Workman et al, 2020), so their absence is not the result of evolutionary constraints.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the precise relationship between CRISPR-Cas reactivity and CRISPR-Cas autoimmunity is unknown. However, we know that an increase in reactivity results in higher autoimmunity (Levy et al, 2015; Workman et al, 2020). In addition, there is limited evidence that an increase in reactivity is proportional to autoimmunity (Levy et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation